2022
DOI: 10.3390/cells11213370
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Regulates Neuronal and Immune Function in the Rat Small Intestine and Colonic Microbiota after Ischemic/Reperfusion Injury

Abstract: Background: Intestinal ischemia and reperfusion (IRI) injury induces acute and long-lasting damage to the neuromuscular compartment and dysmotility. This study aims to evaluate the pathogenetic role of hyaluronan (HA), a glycosaminoglycan component of the extracellular matrix, as a modulator of the enteric neuronal and immune function and of the colonic microbiota during in vivo IRI in the rat small intestine. Methods: mesenteric ischemia was induced in anesthetized adult male rats for 60 min, followed by 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Notably, the histological features of the NMRs small intestine and colon more closely resemble those of bigger rodents, such as rats (69) and guinea pigs (70,71). This is of particular interest because the altered intestinal architecture found in NMRs would not completely explain the increased ileum tissue integrity (reflected as increased in TEER) observed in these animals compared to mice.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the histological features of the NMRs small intestine and colon more closely resemble those of bigger rodents, such as rats (69) and guinea pigs (70,71). This is of particular interest because the altered intestinal architecture found in NMRs would not completely explain the increased ileum tissue integrity (reflected as increased in TEER) observed in these animals compared to mice.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the histological features of the NMRs small intestine and colon more closely resemble those of bigger rodents, such as rats (69) and guinea pigs (70,71). This is of particular interest because the altered intestinal architecture found in NMRs would not completely explain the increased ileum tissue integrity (reflected as increased in TEER)…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of I/R in intestinal tissues can stimulate the release of reactive oxygen species and associated inflammatory mediators, instigating the aggregation and activation of neutrophils within the intestine [ 46 ]. The persistence of activated neutrophils could exacerbate local intestinal damage, culminating in the impairment of the gut barrier and translocation of intestinal bacteria and endotoxins [ 47 , 48 ]. Our prior research on rats revealed that II/R injury could result in intestinal inflammation and a reduction in the levels of tight junction proteins [ 16 ].…”
Section: Discussionmentioning
confidence: 99%